Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.